A temporal analysis of combinations in professional boxing - Harries, N.; O`Donoghue, P. (World Congress of Performance Analysis of Sport IX, 2012)
Previous analysis of boxing performance has shown frequencies of different punch types that are thrown (Hughes and Franks, 1997). However, the frequency profiles of punch types do not provide information on combinations that are used. Therefore, the purpose of the current investigation was to investigate temporal patterns in combinations of 2, 3 and 4 punches used by boxers of three different weight divisions; bantam weight, middle weight and heavy weight. A manual notation system was developed to record single punches and combinations of punched during 8 bouts from each weight division. Punches were classified into 9 different types; jabs (J), left (L), right (R), straight (S), uppercut (U), left to the body (LB), right to the body (RB), jab to the body (JB) and straight to the body (SB). The outcome of each punch was classified as hitting or missing the opponent. There was very good inter-0.923). A spreadsheet was programmed to identify different types of combinations that occurred and a pivot table was used to obtain frequencies of these within each match. Some contests were less than 12 rounds and so values were scaled to allow a meaningful comparison between weight divisions. With 9 punch types, there are a possible 92 + 93 + 94 = 7371 different types of combination. However, over half of the combinations observed fell into the 12 types shown in Table 1. These 12 combination types covered 43.0+9.9% of combinations used by bantam weights, 57.9+19.8% for middle weights and 64.1+10.7% for heavy weights. A Kruskal Wallis H test revealed that the percentage of combinations that were included in these 12 types significantly differed between the three weight categories (p = 0.012). A Wilcoxon signed ranks test revealed that L was significantly more likely to hit the target when used in a combination than in isolation (48.8+24.9% v 45.4+21.2%, p < 0.05). The results show that there are commonly used combinations in boxing with lighter weight boxers tending to use a greater variety of combination types during bouts. The modal combination was J.S. However, J.J was the modal combination for middle-weight boxers. Further research applying temporal analysis is recommended to analyse combinations used in other weight divisions.